Image Brokers : Visualizing World News in the Age of Digital Circulation - Gürsel, Zeynep Devrim (Book collections on Project MUSE., 2016)
"Image Brokers is an in-depth ethnography that reveals the labor and infrastructure behind news images and how they are circulated. Zeynep Devrim Gürsel presents an intimate look at the ways image brokers--the people who manage the distribution or restriction of images--construct and culturally mediate the images they circulate. Through this framework, news images become commodities that impact how politics and culture are visualized in the world. Set against the backdrop of the War on Terror and based on fieldwork conducted at the photojournalism industry's centers of power in New York and Paris, Image Brokers explores the transition from analog to digital technologies and shows how new digital and social media platforms continue to change photojournalism and create ever-widening distribution networks. The book is a powerful investigation of the processes of decision-making amid the changing infrastructures of representation."--Provided by publisher.